2011
DOI: 10.1590/s1981-81222011000200004
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização da atividade pesqueira em Vila do Conde (Barcarena, Pará), no estuário amazônico

Abstract: Resumo: A região de Vila do Conde é um importante pólo industrial no sul da baía de Marajó. Apesar da importância da pesca e da vulnerabilidade da região em relação ao impacto ambiental, não há nenhum estudo aprofundado sobre a pesca e a ictiofauna na área. Abstract: Vila do Conde is an important industrial complex in the south of the Marajó Bay. Despite the important fishery activity and the vulnerability in terms of environmental impacts, no relevant scientific study on fishery and ichthyofauna has been carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 5 publications
0
12
0
7
Order By: Relevance
“…Studies have shown that the inner portion of the Amazon estuary, including Marajó and Guajará bays and the Pará estuary are used by ichthyofauna more for growth and development, rather than reproduction (Viana et al, 2010). In addition to the biological aspects of these phenomena, the local population is economically dependent on local fishery resources (Paz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the inner portion of the Amazon estuary, including Marajó and Guajará bays and the Pará estuary are used by ichthyofauna more for growth and development, rather than reproduction (Viana et al, 2010). In addition to the biological aspects of these phenomena, the local population is economically dependent on local fishery resources (Paz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This study area is an estuarine environment with a considerable freshwater input, being classified as a tidal freshwater estuary according to the scheme of Elliott and McLusky (2002). Despite the intense industrial activity at the estuary of the Pará River, the area is an important artisanal fishing ground and the local population is highly dependent on fishery resources (Paz et al, 2011). In addition to its socio-economic importance, the area plays an important ecological role in the reproduction, feeding and development of many fish species.…”
Section: Introductionmentioning
confidence: 99%
“…Na porção continental, os solos predominantes são o Latossolo Amarelo distrófico, o Podzol Hidromórfico e Concrecionário Laterítico indiscriminado distrófico, textura indiscriminada (EMBRAPA, 2013). Entre as atividades produtivas destaca-se a agricultura, pesca artesanal e a indústria, principalmente pela locação de empresas com beneficiamento de alumínio implantado desde a década de 80 e em contínuo crescimento, decorrente de atividades minero-metalúrgicas e portuárias, sendo esta última devido à criação do Porto da Vila do Conde (Paz et al, 2011).…”
Section: Metodologiaunclassified
“…The Para´River estuary, 40 km west of Bele´m, is an important artisanal fishing area characterised by the presence of several fishing grounds (Paz et al, 2011). This region is also relevant due to the high dependence of the population on the fishing resources.…”
Section: Introductionmentioning
confidence: 99%